Detection and molecular characterisation of extended-spectrum β-lactamase-producing enteric bacteria from pigs and chickens in Nsukka, Nigeria. (December 2018) - Chah, Kennedy F.; Ugwu, Ifeoma C.; Okpala, Angela; Adamu, Kwabugge Y.; Alonso, Carla Andrea; Ceballos, Sara; Nwanta, John N.; Torres, Carmen
Highlights: CTX-M-15 is the main resistance mechanism among ESBL-producing Enterobacteriaceae of food-producing animals in Nigeria. pAmpC β-lactamase CMY-2 is reported for the first time from a food-producing animal in Nigeria. The minor ESBL type VEB is described for the first time in a bacterium of animal origin in Africa ( Providencia spp.). All ESBL/pAmpC-producing enteric bacteria were multidrug-resistant. E. coli belonging to a new sequence type (ST3625) is reported in this study. Abstract: Objectives: This study screened chickens and pigs slaughtered for human consumption for the presence and characteristics of extended-spectrum β-lactamase (ESBL)- and plasmid-encoded AmpC (pAmpC) β-lactamase-producing enteric bacteria. Methods: Faecal samples from 410 broiler chickens and 100 pigs were cultured on MacConkey agar supplemented with 2 μg/mL cefotaxime. Antimicrobial resistance phenotypes of the recovered isolates were determined by disk diffusion. PCR and sequencing were performed to identify the ESBL and pAmpC gene variants and other associated resistance determinants. Genetic diversity of the isolates was analysed by phylotyping and multilocus sequence typing. Results: ESBL-producing Escherichia coli, Klebsiella pneumoniae, Enterobacter asburiae and Providencia spp. were isolated from 17 (4.1%) and 2 (2.0%) of the samples from chickens and pigs, respectively. One pAmpC-producing E. coli isolate was obtained from a chicken. Resistance to tetracycline, trimethoprim/sulfamethoxazole, chloramphenicol and gentamicin was exhibited by 95%, 80%, 60% and 55% of the ESBL/pAmpC-producing strains, respectively. tet (A) and aac(3)-II were the predominant genes detected in tetracycline- and aminoglycoside-resistant strains, respectively. bla CTX-M, encoding CTX-M-15 (15 isolates) or CTX-M-1 variants (3 isolates), was present in all but one ESBL-producer, either alone or in combination with bla SHV and/or bla TEM . The remaining ESBL-producer, a Providencia spp. recovered from a chicken, harboured bla VEB . The only pAmpC-positive E. coli strain carried bla CMY-2 . The 11 ESBL-producing E. coli strains belonged to five lineages (ST226-A, ST3625-B1, ST10-A, ST46-A and ST58-B1). Conclusions: Healthy chickens and pigs act as reservoirs of ESBL/pAmpC-producing enterobacteria that can potentially be transmitted to humans through direct contact or ingestion of contaminated meat.